The impact of salpingectomy and single-dose systemic methotrexate treatments on ovarian reserve in ectopic pregnancy. (October 2016) - Sahin, Cagdas; Taylan, Enes; Akdemir, Ali; Ozgurel, Banu; Taskıran, Dilek; Ergenoglu, Ahmet M.
Abstract: Objective: To investigate the effects of salpingectomy and methotrexate treatments on ovarian reserve in ectopic pregnancy. Study design: In this prospective study, a total of 131 patients with ectopic pregnancy were divided into 3 groups of methotrexate (MTX) only (Group-1, n : 55), salpingectomy only (Group-2, n : 61), and salpingectomy following MTX (Group-3, n : 15). Pretreatment and post-treatment anti-Müllerian hormone (AMH) levels were evaluated. Results: Significant differences in AMH levels were detected between group 1 and group 2 (2.52 ± 1.28 vs. 1.96 ± 1.66, p = 0.043), and group 1 and group 3 (2.52 ± 1.28 vs. 1.77 ± 0.76, p = 0.035) at one month postoperative. However, these differences disappeared at the 3rd postoperative month. When AMH levels were compared within the same group, postoperative one month AMH levels were significantly lower than the preoperative AMH levels only in group 3 ( p = 0.03). However, this difference also disappeared at the 3rd postoperative month. Conclusion: Systemic single-dose methotrexate treatment, unilateral salpingectomy, and salpingectomy following methotrexate administration in ectopic pregnancy were reassuring based on pretreatment and post-treatment AMH levels. Current medical and surgical treatment approaches do not have an obvious negative effect on ovarian reserve.